Un théorème sur l’influence des coefficients sur l’ultraconvergence de la série de Dirichlet - Oskolkov, L. (Lithuanian Mathematical Journal, 1969)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Л. А. Осколков. Одна теорема о влиянии коэффициентов на сверхсходимость ряда ДирихлеL. Oskolkovas. Viena teorema apie koeficientų įtaką Dirichle eilutės virškonvergavimui